Peran BUMDes Dalam Memanfaatkan Dana Desa Untuk Memajukan Kesejahteraan Masyarakat Desa Banyuanyar, Kecamatan Ampel, Kabupaten Boyolali - Tjokro Rahardjo, Yesaya Setia Nugroho; Hapsari, Aprina Nugrahesthy Sulistya (STIE Malangkucecwara, 2019)
The Indonesian government is currently carrying out overall development both in terms of infrastructure and economically for every corner of the region such as in rural areas. This is evidenced by the assistance in the form of village funds which are given annually by the government. Another proof of rural development is the four development programs launched by the Ministry of Village, Development of Disadvantaged Areas and Transmigration, one of them is the development of Village Enterprises (BUMDes). BUMDes are expected to be the main economic foundation for rural areas so that BUMDes can be a source of income for rural development. This study aims to provide information about the role of BUMDes in managing village funds to improve the prosperity of the Banyuanyar Village community, Ampel District, Boyolali Regency. This study uses a qualitative method by collecting data using analytical triangulation techniques. The results of the study show that BUMDes have performed their roles quite well in the welfare of society. The constraints of BUMDes in Banyuanyar Village refer more to the lack of human resources that can process the village's potential and are still skeptical of the village community about BUMDes itself.